Analysis of The Influence of ISO 9001: 2015 Quality Management System Implementation on Employee Performance of PT Fumira Semarang - Syaiful Anwar; Rudi Handoyono; Alvianita Gunawan Putri (Applied Accounting and Management Review (AAMAR), 2025)
This research aims to determine and analyze the effect of implementing the ISO 9001:2015 quality management system on employee performance at the company PT Fumira Semarang. The approach used is a quantitative approach. The population of this research is all employees at PT Fumira Semarang with a sample size of 25 respondents. The data collection technique used is through a questionnaire. The data analysis technique used is multiple linear regression analysis. The research results show that leadership and the process approach partially influence employee performance. Other results show that customer focus, engagement of people, improvement, evidence-based decision making, and relationship management have no effect on employee performance. Simultaneously, the independent variables influence employee performance.